Nanostructured lipid carriers co-encapsulating Apigenin and Melatonin: An innovative strategy against cancer - Lorena Bonilla-Vidal; Marta Świtalska; Marta Espina; Joanna Wietrzyk; María Luisa García; Eliana B Souto; Anna Gliszczyńska; Elena Sánchez-López (Materials & Design)
Cancer affects 9 million people every year constituting one of the main causes of death. However, current treatments are frequently associated with adverse effects and can exhibit limitations in therapeutic efficacy. Therefore, the combination of the pharmaceutical properties of the natural flavone Apigenin (APG) and the neurohormone Melatonin (MEL), could represent a key finding for tumoral processes. However, both possess low aqueous solubility and photosensitivity. To overcome these limitations, APG and MEL are encapsulated into nanostructured lipid carriers (NLC) based on rosehip oil, to increase their bioavailability and efficacy. Optimization, physicochemical characterization, biopharmaceutical behaviour, and in vitro studies were assessed and compared to individually-loaded NLC. Optimized APG-MEL-NLC owned suitable physicochemical properties with an average size below 200 nm, low polydispersity index, negative charge and high encapsulation efficiency. Biopharmaceutical studies demonstrated that both compounds were released from NLC in a prolonged and sustained manner, following a biphasic behaviour with an initial fast release followed by a slow phase. Cytotoxicity studies showed selective cytotoxicity in tumoral cell lines, especially in the leukaemia cells, where co-encapsulation resulted in an additive pharmacological effect against individually loaded NLC. This novel and natural treatment could open a new therapeutical window in cancer treatment.